Translation and cultural adaptation of the stroke impact scale 2.0 (SIS): a quality-of-life scale for stroke - Brandão, Aline Dias; Teixeira, Natasha Bertocco; Brandão, Maria Claudia; Vidotto, Milena Carlos; Jardim, José Roberto; Gazzotti, Mariana Rodrigues (São Paulo Medical Journal, 2018)
BACKGROUND: No specific quality-of-life scale for stroke patients has previously been translated and evaluated for reproducibility, for use in the Portuguese language. Internationally, the instrument for this purpose is the Stroke Impact Scale 2.0 (SIS). Use of of SIS enables comprehensive analysis on the impact of mild and moderate stroke on patients’ lives. The aims here were to translate SIS into Portuguese, adapt it culturally, evaluate its reproducibility and correlate it with SF-36 among stroke patients. DESIGN AND SETTING: Translation and validation study. METHODS: The process of initial and retrograde translation was performed, in addition to cultural adaptation to the Brazilian language and culture. SIS was applied to 40 patients, who answered the questions three times. On the first day, the scale was applied twice by two independent researchers (to evaluate interobserver reproducibility). Fifteen days later, the scale was applied for a third time by another researcher (intraobserver reproducibility). The intraclass correlation coefficient (ICC) was used to measure the reproducibility of the SIS scale. RESULTS: The reproducibility of the whole scale was very good (ICC: 0.73 to 0.99). Intraobserver reproducibility in all domains was also very good (ICC: 0.85 to 0.95). Comparison of SIS with SF-36 showed that the domains of strength, mobility and activities of daily living (ADLs) correlated moderately with the functional capacity domain, as did the ADL domain with general health status. The other correlations were weak. The depression domain showed a moderate negative correlation with the memory and communication domains. CONCLUSION: The translation of the SIS 2.0 scale was easy to understand and it had good reproducibility among stroke patients.